Comparative analysis of the midgut microbiota of two natural tick vectors of Rickettsia rickettsii - Pavanelo, Daniel Brisotto; Schröder, Nicolas C.H.; Pin Viso, Natalia Daniela; Martins, Larissa A.; Malossi, Camila Dantas; Galletti, Maria Fernanda B.M.; Labruna, Marcelo B.; Daffre, Sirlei; Farber, Marisa Diana; Fogaça, Andréa C. (Elsevier, 2020)
Although the ticks Amblyomma sculptum and Amblyomma aureolatum are important vectors of Rickettsia rickettsii, causative agent of the life-threatening Rocky Mountain spotted fever, A. aureolatum is considerably more susceptible to infection than A. sculptum. As the microbiota can interfere with the colonization of arthropod midgut (MG) by pathogens, in the current study we analyzed the MG microbiota of both tick species. Our results revealed that the MG of A. aureolatum harbors a prominent microbiota, while A. sculptum does not. Remarkably, a significant reduction of the bacterial load was recorded in R. rickettsii-infected A. aureolatum. In addition, the taxonomy analysis of the MG bacterial community of A. aureolatum revealed a dominance of the genus Francisella, suggesting an endosymbiosis. This study is the first step in getting insights into the mechanisms underlying the interactions among Amblyomma species, their microbiota and R. rickettsii. Additional studies to better understand these mechanisms are required and may help the development of novel alternatives to block rickettsial transmission.